2006
DOI: 10.4314/njsr.v7i3.12304
|View full text |Cite
|
Sign up to set email alerts
|

Ocular aids: experience at the Guinness Ophthalmic unit, Kaduna , Nigeria

Abstract: Objective: To determine the pattern of presentation of ocular manifestations in HIV/AIDS and the modes of management employed. Method: This collaborative, hospital based retrospective study between the Ophthalmology and Immunology units covered the period between January-December, 2004. Results: 1020 new patients were seen during this period with HIV/AIDS, of whom 125(12.3%) cases presented with some form of ocular complications, made up of 74 females (59.2%) and 51 males (40.8%). Herpes Zoster Ophthalmicus (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 7 publications
0
13
3
Order By: Relevance
“…That study included allergic conjunctivitis and cataract as complications resulting from HIV infection which may have accounted for the higher numbers. Our present finding is also lower than the 25.3% reported by Bekele et al [8] in Jimma, Ethiopia, 12.3% in Northern Nigeria [14], 50% in the US [15], 60% in Morocco [16], and 52% in Brazil [17]. The fewer ocular lesions found in this study could also be attributed to the HIV disease status of our patients.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…That study included allergic conjunctivitis and cataract as complications resulting from HIV infection which may have accounted for the higher numbers. Our present finding is also lower than the 25.3% reported by Bekele et al [8] in Jimma, Ethiopia, 12.3% in Northern Nigeria [14], 50% in the US [15], 60% in Morocco [16], and 52% in Brazil [17]. The fewer ocular lesions found in this study could also be attributed to the HIV disease status of our patients.…”
Section: Discussioncontrasting
confidence: 79%
“…Ayena et al also reported herpes zoster ophthalmicus as the second commonest ocular manifestation of HIV infection in Togo [24]. Kehinde et al, however, reported herpes zoster ophthalmicus as the commonest ocular manifestation in patients with HIV/AIDS infection in Nigeria [14]. The disparities noted above may be due to the fact that the patients were at different stages of immune suppression in different population groups studied.…”
Section: Discussionmentioning
confidence: 99%
“…12,14 Another Nigerian study, carried out by Kehinde et al, reported HIV-/ AIDS-associated ocular manifestations in 12.3% of their study population. 23 In a similar study conducted in India among HIV/AIDS patients on HAART, only eight per cent of the study population had ocular manifestations of the disease. 16 HIV-/AIDS-associated ocular manifestations tend to occur most commonly when the CD4 count drops to < 50/µl.…”
Section: Hiv-/aids-associated Ocular Manifestationsmentioning
confidence: 86%
“…27 Kehinde et al reported that herpes zoster ophthalmicus was the most predominant ocular manifestation in their study population. 23 Yet another Nigerian study, carried out by Nwosu et al, reported that 4 (5.3%) out of 76 ophthalmic patients were HIVpositive. Seventy-five per cent of these had herpes zoster ophthalmicus and 25% had uveitis.…”
Section: Hiv-/aids-associated Ocular Manifestationsmentioning
confidence: 96%
“…1,2 HIV is thought to have started and spread unnoticed through the 1960s and 1970s, developing into epidemic proportions in the 1980s. 1,3 The HIV/AIDs pandemic is currently a global phenomenon that has especially impacted on sub-Saharan Africans because of large numbers of those affected coupled with poverty and illiteracy. 4,5 Infection with HIV and Acquired Immuno-deficiency Disease (AIDs) are among the most difficult challenges facing surgeons worldwide.…”
Section: Introductionmentioning
confidence: 99%